THE EFFECT OF GOOD CORPORATE GOVERNANCE ON THE PROFITABILITY OF MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2016-2020 - Shanti Adrina Rahayu (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this research on corporate governance is to be able to provide information to find out how influential the management system that occurs within a company is on the profits to be obtained by the company. In this study, we will discuss about corporate governance which will be measured using 5 (five) categories of independent variables including the board of commissioners, board of directors, audit committee, management ownership and institutional ownership which will be juxtaposed with the dependent variable, namely return on equity (ROE). The sample population is obtained from financial statement data that has been published by companies on the Indonesia Stock Exchange (IDX) in the research period from 2016 to 2020. The total sample that has been selected according to the criteria is 153 companies. From the research that has been carried out, it shows that the board of commissioners, board of directors, managerial ownership and institutional ownership affect ROE. However, the audit committee seems to have an effect on the ROE variable but it is not significant. Keywords: GCG, Indonesia Stock Exchange, ROE